High pressure coolant ejector for machining - Cheng, Du (2017)
More hardened materials are used and more precision is required on the Machining process. There are many types of machining method in the manufacturing area. This project is studying the turning process with high pressure coolant nozzle. During turning process, the poor machining performances such as bad roughness result or long process time are caused by the heat and friction which is generated between tools and chips in the cutting area. The high-pressure coolant will provide an efficient way to solve it. However, quite a lot of machining industries still using the normal pressure coolants to reduce the friction force & heat at the cutting area. The default way for the most machine is to use normal coolant. The high-pressure nozzle system needs to be installed if use the high-pressure coolant. This project fabricated a high-pressure nozzle to analyze the high-pressure coolant effect. Firstly, a high-pressure nozzle, as well as tool holders for nozzle and cutter respectively was designed and fabricated. The high-pressure pump can provide coolant with the maximum pressure of 35 Psi to the turning machine via the hydric pipe, but there is some loss in the pressure. The report presents total 9 times of cutting, 2 types of wet cutting operation and 1 set of dry conditions cutting operation. The cutting force and friction force was detected and analyzed by the Kistler device. The machining parameters are kept constant in all the experiments and only the coolant type was changed according to the experiment design. The purpose of this experiment is to investigate the effect of high-pressure nozzle and coolant on cutting forces, cutting chip shapes and the surface quality. With the experiment result, it is shown that the high-pressure coolant nozzle will improve the surface quality. The cutting force vibration is significantly decreased. The average force level does not change significantly. The chip length is reduced with the use of high-pressure coolant nozzle.